Gestión de ventas para la Ferretería “Big Market” ubicada en la ciudad de Babahoyo, periodo 2022. - Morales Moran, Alisson Gabriela (2023)
In the present case study, it will be based on the way to manage the commercialization of hardware businesses, which focuses on the objective of analyzing the sales management of the "BIG MARKET" hardware store in the city of Babahoyo for the period 2022, to the increase in sales, this through the identification of important factors that allow to have a real perspective on the procedures that must be executed in the commercial area. Therefore, this type of analytical work focuses on developing the conceptualization of the problems presented in the case study with the purpose of proposing alternatives that allow solving the existing shortcomings in sales management and this would lead to the Big Market hardware store Have an analysis study that allows you to study the behavior of the processes that are related to the commercial area in order to make appropriate decisions for the continuous improvement of your procedures to make the business profitable and competitive within the babahoyense commercial market.